Energetics of lanthanide cobalt perovskites: LnCoO3−δ (Ln = La, Nd, Sm, Gd). Issue 38 (28th August 2015) - Sahu, Sulata Kumari; Tanasescu, Speranta; Scherrer, Barbara; Marinescu, Cornelia; Navrotsky, Alexandra
Abstract : The thermodynamic stability of lanthanide cobaltites is also a function of their existing oxygen non-stoichiometry. Abstract : Lanthanide cobalt perovskites LnCoO3− δ (Ln = La, Nd, Sm, and Gd) are important materials for electroceramics, catalysts, and electrodes in solid oxide fuel cells. Formation enthalpies of LnCoO3− δ compounds were measured using high temperature oxide melt solution calorimetry. The formation enthalpies of LaCoO2.992, NdCoO2.985, SmCoO2.982 and GdCoO2.968 from constituent binary oxides (Ln2 O3, CoO) and O2 gas are −111.87 ± 1.36, −98.49 ± 1.33, −91.56 ± 1.46 and −88.16 ± 1.45 kJ mol −1, respectively. Thus these perovskites become energetically less stable with decrease in ionic radius of the lanthanide (from La to Gd), which corresponds to a decreasing tolerance factor and increasing oxygen deficiency. The thermodynamic stability of LaCoO2.992, NdCoO2.985, SmCoO2.982 and GdCoO2.968 was also assessed considering their oxygen partial pressures for decomposition, with good agreement between thermochemical and equilibrium data.